A study on customers satisfaction with Sibu Post Office counter services / Rajak@Abdul Razak Amin - Amin, Rajak@Abdul Razak (2002)
The study is based on customer satisfaction with Sibu Post Office Counter Services, where it is the sole processing outlet for postal services other than providing SBBS Counters for various agencies such as Telekom Malaysia, Sibu Water Board, SESCo, Astro and etc. The study is based on primary data and secondary data. For primary data, the researcher had conducted interviews with the staff and customers; respondents through questionnaires; and secondary data through annual report, journals, articles in newspapers, as well as Internet. The researcher will comment on the system used by SPO with other companies operating the SBBS Counters in gauging its efficiency of its similar services. Strategic location at the town centre and the economic environment in Sarawak plays an important role in the demand for its services. On the other hand, the presence of competitors in the market diminishes the market shares of the product. Lastly, the researcher put up suggestions on how to improve the marketing edge of the company in marketing services to the public in Sibu.